Udział ziemian w wileńskich towarzystwach rolniczych i technicznych na początku XX w. - Ilgiewicz, Henryka (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Vilnius agricultural society was established in 1899. In the same time there were founded some departments of Russian societies, which had a goal to make the economical life in the region more dynamic. There were: Vilnius Department of Russian Technical Society (Виленское отделение Императорского русского технического общества, 1897–1915), Vilnius Department of Russian Imperial Society of Gardening (Виленский отдел Императорского российс- кого общества плодоводства, 1897–1915), as well as Vilnius Department of Russian Imperial Society of Pisciculture and Fishing (Виленский отдел Императорского российского общества рыбоводства и рыболовства, 1900–1915). In 1905 by an initiative of Polish engineers was founded Vilnius Technical Society. In all these societies worked numerous representatives of Polish landowners and intellectuals. The largest number of Poles was in Vilnius Agricultural Society the least one was in Vilnius Department of the Russian Technical Society. An experience, received during the work in mentioned above societies, Poles have used later in other activities in social and political life.